1984
DOI: 10.1002/hep.1840040527
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Vaccination: The Response of Patients with Alcoholic Liver Cirrhosis

Abstract: Patients with cirrhosis have an increased risk of dying from pneumococcal pneumonia. Their immunological response to pneumococcal vaccination is not known. We compared the antibody response to challenge with a 14-valent purified pneumococcal polysaccharide vaccine in 15 patients with biopsy-proven alcoholic liver cirrhosis, 10 healthy volunteers and 10 patients with chronic obstructive pulmonary disease. Preimmunization levels for Danish type 1 pneumococcal polysaccharide were lower among cirrhotics than patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

1986
1986
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 19 publications
0
8
0
4
Order By: Relevance
“…Adequate response to pneumococcal vaccine has been established in patients with alcoholic liver disease (19), although similar data are lacking for influenza vaccination. Anti-HAV seroconversion rates are 94 to 98% among patients with compensated liver disease (20,21) and 66% among those with decompensated disease (21).…”
Section: Discussionmentioning
confidence: 99%
“…Adequate response to pneumococcal vaccine has been established in patients with alcoholic liver disease (19), although similar data are lacking for influenza vaccination. Anti-HAV seroconversion rates are 94 to 98% among patients with compensated liver disease (20,21) and 66% among those with decompensated disease (21).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic active hepatitis and primary biliary cirrhosis also predispose to pneumococcal infections, although they are not associated with alcoholism. The antibody response and opsonic titres of cirrhotic patients after inoculation shows an adequate response to the pneumococcal vaccine (Pirovino et al 1984), but its clinical efficacy remains to be proven (Simberkoff et al 1983). …”
Section: Hepatic Diseasementioning
confidence: 98%
“…Early studies in patients with cirrhosis showed good response to the pneumococcal vaccine. Patients with alcoholic cirrhosis produced adequate titers at 3 months with a 14-valent polysaccharide vaccine (83). Increased antibody and opsonic titers were demonstrated in both serum and ascitic fluids (92).…”
Section: Pneumococcal Vaccinementioning
confidence: 99%